Brazil - Piaui State Economic Memorandum : Managing a Natural Inheritance - World Bank (Washington DC, 2013)
This report represents a snapshot of a dialogue between the State of Piaui and the World Bank and focuses on the strategies and actions the State Government may wish to adopt. Piaui's challenge is to build institutions that address its weaknesses and exploit its strengths. Addressing weaknesses implies continuing with efforts to improve education, raising productivity in small-scale agriculture, increasing public participation in government decisions, and enhancing the administration of taxation and spending. Exploiting strengths implies fortifying the management of land, water, and natural resources, carefully selecting strategic infrastructure investments, and recognizing and taking strategic decisions to "get ahead of the environmental frontier" in several parts of the state. Based on the relevant geographical traits of Piaui, three chapters are devoted to the geographical regions: the cerrados, the semi-arid southeastern region, and the north of the state. The report relates cross-cutting institutional themes (a) the revised role of the State in Piaui, (b) fiscal aspects including taxation and spending, (c) options in education, and (d) an outline of action plan for building participatory mechanisms for consultation between government and civil society. The conclusion gives a general framework of strategic options for poverty reduction in Piaui including the Bank's suggestions of priorities, timescales, and approximate costs where possible.